Comparative analysis of shear bond strength of MTA and Theracal PT with different restorative materials - Gözde Ece Karaman; Müge Bulut; Elif Yazan Sukur (BMC, 2024)
Abstract Background This study aimed to compare the in vitro shear bond strength (SBS) of mineral trioxide aggregate (MTA) and dual-cured, resin-modified calcium silicate material (Theracal PT) to composite resin, compomer, and bulk-fill composite, and to evaluate the bond failure mode under a stereomicroscope. Methods Ninety acrylic specimens, each with a 4 mm diameter and 2 mm height central hole, were prepared. These specimens were randomly divided into two groups based on the capping materials: MTA and Theracal PT. Each group was further subdivided into three subgroups (n = 15) according to the restorative materials: composite resin, compomer, and bulk-fill composite. The specimens were then subjected to shear testing using a universal testing machine at a crosshead speed of 1 mm/min. Post-test, the fracture locations were examined using a stereomicroscope. Data were analyzed using a two-way analysis of variance (ANOVA) and the Tukey test. Results The SBS values for the Theracal PT group were significantly higher than those for the MTA group (p < 0.001). Within the MTA groups, no significant differences were observed in SBS values across the different restorative materials. However, a significant difference was found between the mean SBS values of the Theracal PT + composite resin group and the Theracal PT + compomer group (p < 0.001). Conclusions Theracal PT shows promise in dentistry due to its superior bond strength. Given its bond values, Theracal PT appears capable of forming durable and long-lasting restorations by establishing reliable bonds with various restorative materials commonly used in dentistry.